CHARACTERISATION AND CORRELATION OF ACTIVE HYDROCARBON SEEPAGE USING GEOPHYSICAL DATA SETS: AN EXAMPLE FROM THE TROPICAL, CARBONATE YAMPI SHELF, NORTHWEST AUSTRALIA - Rollet N.; Logan G.A.; Kennard J.M.; O'Brien P.E.; Jones A.T.; Sexton M. (My University, 2006)
For the first time in Australia, active present-day hydrocarbon seepage has been imaged - on the tropical carbonate Yampi Shelf, in 50 and 90 m water depth. Seepage is evidenced by gas plumes in the water column that are associated with seabed features, such as clusters of reflective blocks, hard-grounds, pockmark fields, and mounds. Seepage activity and intensity seems to vary with changes in pressure related to macro-tidal cycles. The seabed features coincide with sub-surface features such as areas of seismic signal attenuation under high amplitude reflectors, seismic discontinuities and bright spots. Hydrocarbon migration-seepage pathways appear to be controlled by the reactivation of pre-existing fractures and dykes within the basement. The types of seabed features and their preservation on a tropical carbonate shelf are strongly influenced by the coarse bioclastic nature of sediments and the high energy of macro-tidal currents and storm reworking. © 2005 Published by Elsevier Ltd.
Keywords: CARBONATE MOUNDS; HYDROCARBON LEAKAGE; POCKMARKS; SEEP DETECTION